Perception of social cues of danger in autism spectrum disorders. - Nicole R Zürcher (Public Library of Science (PLoS), 2013)
Intuitive grasping of the meaning of subtle social cues is particularly affected in autism spectrum disorders (ASD). Despite their relevance in social communication, the effect of averted gaze in fearful faces in conveying a signal of environmental threat has not been investigated using real face stimuli in adults with ASD. Here, using functional MRI, we show that briefly presented fearful faces with averted gaze, previously shown to be a strong communicative signal of environmental danger, produce different patterns of brain activation than fearful faces with direct gaze in a group of 26 normally intelligent adults with ASD compared with 26 matched controls. While implicit cue of threat produces brain activation in attention, emotion processing and mental state attribution networks in controls, this effect is absent in individuals with ASD. Instead, individuals with ASD show activation in the subcortical face-processing system in response to direct eye contact. An effect of differences in looking behavior was excluded in a separate eye tracking experiment. Our data suggest that individuals with ASD are more sensitive to direct eye contact than to social signals of danger conveyed by averted fearful gaze.